Burkholderia pseudomallei and melioidosis - Meumann, EM; Limmathurotsakul, D; Dunachie, SJ; Wiersinga, WJ; Currie, BJ (Springer Nature, 2023)
Burkholderia pseudomallei, the causative agent of melioidosis, is found in soil and water of tropical and subtropical regions globally. Modelled estimates of the global burden predict that melioidosis remains vastly under-reported, and a call has been made for it to be recognized as a neglected tropical disease by the World Health Organization. Severe weather events and environmental disturbance are associated with increased case numbers, and it is anticipated that, in some regions, cases will increase in association with climate change. Genomic epidemiological investigations have confirmed B. pseudomallei endemicity in newly recognized regions, including the southern United States. Melioidosis follows environmental exposure to B. pseudomallei and is associated with comorbidities that affect the immune response, such as diabetes, and with socioeconomic disadvantage. Several vaccine candidates are ready for phase I clinical trials. In this Review, we explore the global burden, epidemiology and pathophysiology of B. pseudomallei as well as current diagnostics, treatment recommendations and preventive measures, highlighting research needs and priorities.